Characterization, influence and manipulation of the gastrointestinal microbiota in health and disease - García Mazcorro, José Francisco; Garza González, Elvira; Marroquín Cardona, Alicia Guadalupe; Tamayo, José L. (2015)
The gastrointestinal tract harbors trillions of microorganisms that are indispensable for health. The gastrointestinal microbiota can be studied using culture and molecular methods. The applications of massive sequencing are constantly increasing, due to their high yield, increasingly accessible costs, and the availability of free software for data analysis. The present article provides a detailed review of a large number of studies on the gastrointestinal microbiota and its influence on human health; particular emphasis is placed on the evidence suggesting a relationship between the gastrointestinal microbial ecosystem and diverse physiological and immune/inflammatory processes. Discussion of the articles analyzed combines a medical approach and current concepts of microbial molecular ecology. The present revision aims to be useful to those interested in the gastrointestinal microbiota and its possible alteration to maintain, re-establish and enhance health in the human host.